Membangun Peradaban dengan Epistemologi Baru: Membaca Pemikiran Said Nursi - Akhmad Rizqon Khamami (Universitas Darussalam Gontor, 2015)
There are three models of approaches to modernity that was born in the West; 1) accepting it by taken for granted, 2) rejecting it, and 3) trying to find a new alternative in addition to the Western civilization with the spirit of re-establishing the practice of ijtihad, erasing taklid, and returning to al-Quran and al-Sunnah. This article discussed the idea of Said Nursi in the reconciliation of science and Islam. It offered an epistemological approach that integrates Islam and science. The author attempted to break the academic problem and borrowed Ian Barbour’s approach. Four reactions that occur as a result of the encounter of science and religion: conflict, independence, dialogue, and integration. The theory states that the first step to make the integration go smoothly is removing science from materialist philosophy. This step is performed by Nursi. Nursi built a new epistemology as an offer to the condition of Muslims, who at that time should redevelop the civilization which was left behind by European nations. Nursi reconciled Islam and science towards integrity. Nursi was against Materialism for the first step. Secondly, he put the al-Qur’an as the highest source of science. By making the method of science under the principles and worldview of the al-Qur’an, it can change the modern scientific understanding of the universe to be in accordance with the description of the al-Qur’an.